Analisis Kesantunan Berbahasa Berbasis Gender dalam Komunikasi Pembelajaran Bahasa Indonesia di Muslim Santitham Foundation School Thailand - Lestari, Oktavia Winda; Maulida, Siti Zumrotul; Masmumat, Malinee; Husin, Norhazlina (MARDIBASA: Jurnal Pembelajaran Bahasa dan Sastra Indonesia, 2025)
Gender-Based Language Politeness in Indonesian Language Learning Communication is very important to do because it can help understand how gender differences affect the use of language and politeness in learning communication. In addition, it can increase the effectiveness of Indonesian language learning and reduce gender gaps in education. The descriptive qualitative research aims to explain the existence of the principle of politeness of students language to teachers based on gender in Indonesian language learning communication in class X of Islamic Santitham Foundation School. Direct observation and recording are data collection techniques and data analysis starting form recording and direct observation for three months with an analysis structure, namely, identifying data, classifying data, clarifying data and conclusions. The results of the study stated that male students to female teachers are more often obedient in language than to male teachers. Likewise, female students are more often obedient in language to female teachers than to male teachers. The communication of impoliteness to male teachers using ordinary communication. Both findings are also influenced by the factor of separation or distance between men and women in the scope of Islamic Santitham Foundation School.